2017
DOI: 10.1016/j.ymthe.2017.01.012
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Cardiac Anti-miR-208a Therapy Is Stress Dependent

Abstract: MicroRNAs (miRNAs) are important regulators of biology and disease. Recent animal efficacy studies validate the therapeutic benefit of miRNA modulation and underscore the therapeutic value of miRNA-targeting oligonucleotides. However, whether disease conditions (stress) influence the pharmacological effects of an anti-miR is currently unknown. To study the effect of disease on target regulation after anti-miR treatment, we injected animals with anti-miR-208a, a synthetic oligonucleotide that inhibits the cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…Other variables such as the use of medication or having comorbidities could also affect biomarker results or treatment efficiency. Furthermore, related to therapies, disease conditions have been shown to increase pharmacological effects of antagomiRs [ 145 ]. The disease severity and type could therefore influence therapeutic actions of miR-related therapies.…”
Section: Limitations and Future Perspectivesmentioning
confidence: 99%
“…Other variables such as the use of medication or having comorbidities could also affect biomarker results or treatment efficiency. Furthermore, related to therapies, disease conditions have been shown to increase pharmacological effects of antagomiRs [ 145 ]. The disease severity and type could therefore influence therapeutic actions of miR-related therapies.…”
Section: Limitations and Future Perspectivesmentioning
confidence: 99%
“…As an example, mRNA 3D configuration can affect the accessibility of the RISC-binding site 59 . Increasing evidence shows that binding of a miRNA to its mRNA targets can be cell type and environment dependent 60 and that this can be relevant for anti-miRNA cardiovascular therapies 61 . This was already exemplified by Eding et al., 61 who found that, upon in vivo inhibition of the cardiomyocyte-specific miR-208a, the quality and quantity of direct targets of miR-208a that are expressionally modulated depend on the presence and type of cardiac stresses, such as hypertension or myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence shows that binding of a miRNA to its mRNA targets can be cell type and environment dependent 60 and that this can be relevant for anti-miRNA cardiovascular therapies 61 . This was already exemplified by Eding et al., 61 who found that, upon in vivo inhibition of the cardiomyocyte-specific miR-208a, the quality and quantity of direct targets of miR-208a that are expressionally modulated depend on the presence and type of cardiac stresses, such as hypertension or myocardial infarction. The anti-miR-208 treatment in healthy and diseased hearts revealed 3 subsets of targets: (1) health-specific targets, (2) disease-specific targets, and (3) targets common to health and disease.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it was shown that silencing miR-208a expression in the hearts of Dahl salt-sensitive rats improves cardiac function [181]. The efficacy of anti-miR-208a therapy was found to be dependent on the stage of disease [182].…”
Section: Regulation Of Gene Expression By Small Non-coding Rnasmentioning
confidence: 99%